Development of Podcast-Based Irrational Belief Disputing Media to Increase Confidence of Body Shaming Victims in High School Students - Wulandari, Rintiarni Restu; Atmoko, Adi; Rahman, Diniy Hidayatur; Lim, Chea; Dewanti, Septinda Rima (Buletin Konseling Inovatif, 2025)
This research and development aims to produce a podcast-based disputing irrational belief media to increase the self-confidence for victims of body shaming in high school students. This podcast is named the #PULIH podcast which is an audio visual medium and can be listened to independently through the Youtube platform. The #PULIH podcast consists of five episodes with different topics. Each episode discusses the aspect that will be changed, namely the perception of the physical by using the technique of disputing irrational belief. This research and development adapts the five stages of the Borg and Gall development model, namely the information collecting stage, planning stage, prototype development stage, initial field trial, and product revision stage. The initial field trial has three stages, namely the material expert test, the media expert test and the prospective user (student) test. The purpose of the assessment of experts and prospective users to determine the acceptability of the media which includes aspects of accuracy, usability, convenience, and attractiveness. Data analysis using the inter-rater agreement. The results of the expert and prospective user tests overall show a very high validation index. It is concluded that the podcast-based disputing irrational belief media is very appropriate, useful, easy, and interesting to increase the self-confidence for victims of body shaming in high school students.